2021
DOI: 10.1088/1742-6596/1738/1/012103
|View full text |Cite
|
Sign up to set email alerts
|

A router abnormal traffic detection strategy based on active defense

Abstract: With the rapid development of network attacks, traditional security protection technology is difficult to deal with unknown threats and persistent attacks. Active defense improves the ability to defend against network attacks by building a dynamic, heterogeneous and redundant endogenous security system. Aiming at the problem of single abnormal arbitrament information of routers in mimic defense, a router abnormal traffic detection strategy based on active defense is proposed. By clustering the traffic informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…They found that the technique effectively identified LDDoS. Li et al [12] proposed an active defense-based router anomaly traffic detection strategy for the problem of single router anomaly arbitration information in mimetic defense and found through experiments that the method effectively detected network attacks. Ding et al [13] designed an efficient bi-directional simple recurrent unit (BiSRU) and compressed the original high-dimensional features by stacked sparse autoencoder (sSAE).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the technique effectively identified LDDoS. Li et al [12] proposed an active defense-based router anomaly traffic detection strategy for the problem of single router anomaly arbitration information in mimetic defense and found through experiments that the method effectively detected network attacks. Ding et al [13] designed an efficient bi-directional simple recurrent unit (BiSRU) and compressed the original high-dimensional features by stacked sparse autoencoder (sSAE).…”
Section: Introductionmentioning
confidence: 99%